Cast in permanent ferrocement formwork for concrete beams and columns - Mostrales, Daniel S. (Asia-Pacific Journal of Science, Mathematics, and Engineering, 2014)
This study was done to evaluate the viability of using ferrocement technology as cast for concrete beams and columns. The evaluation followed four phases: preliminary, design, construction, and application phases. A modified reinforcement design of beam and column was processed in the preliminary phase. In the design stage, parameters were set, the possible loads determined and materials tested. Construction phase includes the load testing of the fabricated 200mm x 300mm x 200mm beam samples using Reaction Frame Test (RFT). An application phase is the construction of a new proposed system to actual and compared this to the conventional system. Results showed that ferrocement as formwork is viable and ahs achieved the necessary requirements of a good formwork this study must have. Furthermore, economic efficiency goes beyond what is expected, granted that the new system is done in considering the project in its entirety and that procedures and manual according ti this study are properly followed.